Assessment of the Level of Clinical Preparedness amongst EMS Professionals in Managing Life Threatening Emergencies in Suspected Covid 19 Patients - Parag Rishipathak; hrimathy Vijayraghavan; Anand Hinduja; Prerana Dongre (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: SARS-CoV-2 virus has infected millions of people worldwide and has claimed lakhs of lives in its wake. The sudden onset of the pandemic has led to increased levels of anxiety and depression amongst healthcare workers. EMS professionals are the first responders and need to provide emergency Medical Care to their patients. They are required to perform lifesaving interventions in a short period of time. As it is not possible to ascertain the Covid status of the patient, hence EMS professionals are at the greatest risk of getting infected. The study aims to assess the level of clinical preparedness of EMS professionals and suggests recommendations to improve upon it. Objective: To assess the level of clinical preparedness amongst EMS professionals in tackling life threatening emergencies in suspected Covid 19 patients. Methodology: The study was conducted amongst 150 Emergency Medical Professionals in Pune, India. Respondents were asked to respond to each item using 5 point Likert scale. The Questionnaire was administered to the respondents through online mode after obtaining informed consent. Responding to all questions was mandatory. The respondents were given a period of two days to fill the questionnaire.Discussion: The present study was aimed at examining the current level of preparedness with regards to the disease after nearly a year of the pandemic. The result obtained in terms of knowledge were encouraging and pointed to the fact that the EMS professionals had received adequate training in identification of suspected cases and their initial management. Majority of the respondents suffered from high grade anxiety of contracting the infection. The study highlights the urgent need to conduct counselling and stress management sessions for better mental health of EMS professionals and showed that hospitals are slowly but steadily devising appropriate protocols and safety measures to protect their employees. Conclusion: The contribution of EMS professionals in providing emergency lifesaving care to suspected Covid 19 patients cannot be over emphasized. As the pandemic continues it is essential to ensure the mental and physical of all healthcare professionals. The study is a small attempt to portray the level of knowledge and mental attitude amongst EMS professionals. The findings need to be corroborated with a larger multicentric study.